Comparative analysis of nine Tilletia indica genomes for the development of novel microsatellite markers for genetic diversity and population structure analysis - Kashyap, Prem Lal; Kumar, Sudheer; Kumar, Ravi Shekhar; Sharma, Anju; Khanna, Annie; Kajal,; Raj, Shubham; Jasrotia, Poonam; Singh, Gyanendra (Frontiers in Microbiology, 2023)
Karnal bunt (KB; Tilletia indica) is the prime quarantine concern for quality wheat production throughout the world. The most effective approach to dealing with this biotic stress is to breed KB-resistant wheat varieties, which warrants a better understanding of T. indica genome architecture. In India, the North Western Plain Zone is the prime hot spot for KB disease, but only limited efforts have been made to decipher T. indica diversity at the genomic level. Microsatellites offer a powerful and robust typing system for the characterization and genetic diversity assessment of plant pathogens. At present, inadequate information is available with respect to the development of genome-derived markers for revealing genetic variability in T. indica populations. In current research, nine complete genome sequences of T. indica (PSWKBGH_1, PSWKBGH_2, PSWKBGD_1_3, RAKB_UP_1, TiK_1, Tik, DAOMC236408, DAOMC236414, and DAOMC236416) that exist in the public domain were explored to know the dynamic distribution of microsatellites. Comparative genome analysis revealed a high level of relative abundance and relative density of microsatellites in the PSWKBGH_1 genome in contrast to other genomes. No significant correlation between microsatellite distribution for GC content and genome size was established. All the genomes showed the dominance of tri-nucleotide motifs, followed by mono-, di-, tetra-, hexa-, and penta-nucleotide motifs. Out of 50 tested markers, 36 showed successful amplification in T. indica isolates and produced 52 different alleles. A PCR assay along with analysis of the polymorphic information content (PIC) revealed 10 markers as neutral and polymorphic loci (PIC 0.37). The identified polymorphic SSR loci grouped a geographically distinct T. indica population of 50 isolates representing seven Indian regions (Jammu, Himachal Pradesh, Punjab, Haryana, Uttarakhand, Uttar Pradesh, and Rajasthan) into four distinct clusters. The results of the analysis of molecular variance identified 94% genetic variation within the population and 6% among the population. Structure analysis also confirmed the existence of four genetically diverse groups containing admixtures of T. indica isolates across populations. In nutshell, the current study was successful in identifying novel, neutral and polymorphic microsatellite markers that will be valuable in offering deep insight into the evolutionary relationship and dynamics of the T. indica population for devising effective KB management strategies in wheat.